PENGARUH ABU BATUBARA TERHADAP PERBAIKAN SIFAT KIMIA TANAH DI KALIMANTAN SELATAN - Bambang Joko Priatmadi; Akhmad Rizalli Saidy; Meldia Septiana (BUANA SAINS, 2014)
The use of fly ash as a material for amelioration has been applied in some countries. Fly ash is amorphous compound of silicate-aluminum-iron that contains essential nutrients for plants. Fly ash has a pH of about 8.5 and has chemical properties that can be used as a source of neutralizing acidity in the soil. This study aims to determine the effect of fly ash as a soil ameliorant of soil on dry land and paddy soil in Kalimantan Selatan . Soil samples on dry land were taken from Sungai Riam, Tanah Laut Regency. Soil samples on paddy soils were taken from Sungai Rangas, Banjar Regency. Six kilograms of each soil samples placed on 8-L pots. Fly ash is added to each pot with a dose of 0, 25, 50 and 75 tons ha-1. All treatments were made in four replicates using completely randomized design. Data were collected for soil pH, total-N, total-K, total-P, and cation exchange capacity. The results showed that only the soil pH and soil CEC significantly affected by the addition of fly ash. Application of fly ash by the number 50 - 75 tons per hectare compare 25 tons per ha does not provide a significantly difference to pH and CEC